DETECTION OF DANGEROUS FOOD ADDITIVE IN TAKJIL SNACKS DURING OF RAMADHAN - Irfandi, Ahmad; Simatupang, Meithyra Melviana; Veronika, Erna; Azteria, Veza (Universitas Medan Area, 2024)
Food is a basic human need, necessary to meet daily needs. Human health is greatly influenced by what they consume. Food products added dangerous ingredients can cause serious health effects for humans. The aim of this research was to detect substances of formaldehyde and borax in snacks in the month of Ramadhan (takjil) at Bekasi City. This was descriptive observational research design by direct examination for formalin and borax from the food samples. The population in this study were all traders who sold Takjil on the roadsides in Bekasi City. Sample selected used an incidental sampling technique by taking 8 food samples which. Based on references, they were proven to contain dangerous chemicals. Based on the research results, 2 food samples were found positive containing dangerous food additives, namely 1 sample of lontong (12.5%) was positive for containing borax and 1 sample of martabak tofu (12.5%) was positive for containing Formalin. Seasonal traders who Sell ​​Takjil food during the month of Ramadan may not necessarily be safe. Therefore, it is recommended that health workers from Puskesmas must frequently inspect the food products and socialize the importance of using safe food additives.